Negotiation Between Patuntung and Islam in Kajang, South Sulawesi, Indonesia - Malliongi, Muhammad Takbir; Septiwiharti, Dwi; Nurbaety, Andi; Hak, Imamul; Ibrahim, Ibrahim (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This research examines the relationship between Islam as a world religion and Patuntung as a traditional religion adhered to by the Ammatoa indigenous community in Kajang, South Sulawesi. The relationship between these two religions is not only oppositional or harmonious but also dynamic and negotiating. This research uses a qualitative method with a 'New Ethnography' approach, which pays attention to three aspects: self-reflection, polyvocality, and testimony. The findings of this research show that the meeting between Islam and Patuntung produces a hybrid reality, namely Sallang, which is basically a different Islam and another Patuntung. Sallang is a new reality that emerged from the meeting between Islam and Patuntung. This is clearly seen from Ammatoa's belief that the Koran is 40 juz, 10 juz revealed in Kajang, and 30 juz revealed in Mecca. This research provides a new contribution to the study of the relationship between world religions and indigenous religions, especially in Indonesia.